Potencial del guacimo (Guazuma ulmifolia) en sistemas silvopastoriles (1994)
This article describes the forage potential of guacimo (Guazuma ulmifoTia) as a base component ln the silvopastoral systems for the northern region of Colombia. It is estimated that there are around 15,000 ha in silvopastoral systems in this dry tropical forest, based on a wide variety of trees, coming from natural regeneration and deliberate thinning. An evaluation was made under natural conditions taking into account tree size and density. The trees were grouped together by size: large (crown 2,34m), medium . (crown 2,35 -1,2m) and small (crown 1,2m) and total biomass production, chemical composition and ruminal parameters where evaluated.